2015
DOI: 10.1007/s00894-015-2605-5
|View full text |Cite
|
Sign up to set email alerts
|

The structure of adsorbed cyclic chains

Abstract: In order to determine the structure of polymer films formed of cyclic chains (rings) we developed and studied a simple coarse-grained model. Our main goal was to check how the percolation and jamming thresholds in such a system were related to the thresholds obtained for linear flexible chains system, i.e., how the geometry of objects influenced both thresholds. All atomic details were suppressed and polymers were represented as a sequence of identical beads and the chains were embedded to a square lattice (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…However, in the lateral direction, the closed architecture induces that the ring polymers cannot extend as well as linear polymers, resulting in the slightly smaller R g∥,r compared with R g∥,l . Moreover, the obstacles on the rough surface do not affect the adsorbed conformation of ring polymers and the radius of gyration of ring polymers ( R g,r ) scales with the chain length ( N ) as R g,r ∼ N 0.75 , which coincides well with other investigations. , …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, in the lateral direction, the closed architecture induces that the ring polymers cannot extend as well as linear polymers, resulting in the slightly smaller R g∥,r compared with R g∥,l . Moreover, the obstacles on the rough surface do not affect the adsorbed conformation of ring polymers and the radius of gyration of ring polymers ( R g,r ) scales with the chain length ( N ) as R g,r ∼ N 0.75 , which coincides well with other investigations. , …”
Section: Resultssupporting
confidence: 90%
“…Moreover, the obstacles on the rough surface do not affect the adsorbed conformation of ring polymers and the radius of gyration of ring polymers (R g,r ) scales with the chain length (N) as R g,r ∼ N 0.75 , which coincides well with other investigations. 39,40 Subsequently, we explore the diffusion and the relaxation behaviors of ring polymers adsorbed on the rough surface with d = 4 and h = 1.2. The diffusion coefficient (D) is calculated by the Stocks−Einstein equation (MSD = 6Dt) through extracting a linear segment of MSD(t) curves to illustrate the diffusion behaviors, 41 where MSD is the mean-square displacement of center of mass of polymer chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One can observe that at low polymer concentrations in the cases of polydispersity under consideration the size of a chain scales as < R g 2 > ≈ N 2 ν for chains with N > 20 similarly to monodisperse systems. [ 49 ] Moreover, there are almost no differences in the scaling behavior of R g 2 for all polydispersities studied and therefore we present the results of the uniform distribution only. The scaling exponent was found to be 2 ν = 1.45 ± 0.01 for shorter chains at a low polymer concentration ( φ = 0.1).…”
Section: Resultsmentioning
confidence: 99%
“…[ 28,42,47 ] The infl uence of the macromolecular architecture (linear chains, star-branched chains with a different number of branches and cyclic chains) on the percolation and jamming thresholds is found to be surprisingly weak. [ 28,48,49 ] It has also been shown that the percolation threshold is connected to the structure of chains and their fractal dimension. [ 47,48 ] The other simulation method is based on particle motion in a polymeric system represented by random walks.…”
Section: Macromolecular Theory and Simulationsmentioning
confidence: 99%
“…When one looks at systems containing short flexible chains the percolation threshold decreases with the increase in the chain's length while for semiflexible chains it exhibits a minimum for considerably long polymers . The influence of the macromolecular architecture (linear chains, star‐branched chains with a different number of branches and cyclic chains) on the percolation and jamming thresholds is found to be surprisingly weak . It has also been shown that the percolation threshold is connected to the structure of chains and their fractal dimension .…”
Section: Introductionmentioning
confidence: 99%